The Moderating Effects of Disability on Mobile Internet Use Among Older Adults: Population-Based Cross-sectional Study - Eunjin Yang; Kyung Hee Lee (JMIR Publications, 2022)
BackgroundThe preferred devices to access the internet are changing from personal computers to mobile devices, and the number of older adults with or without disabilities is rapidly increasing in an aging society. However, little is known about the moderating effects of disability on mobile internet use among older adults. ObjectiveThis study aimed to examine the levels of mobile internet use and factors associated with this use among older adults according to their disabilities. In addition, moderating effects of disability on mobile internet use were investigated. MethodsThis study consisted of a secondary data analysis using the 2020 Digital Divide Survey conducted in South Korea. The single inclusion criterion was participants being aged 55 years or older; accordingly, 2243 people without disabilities and 1386 people with disabilities were included in the study. Multiple regression analyses considering complex sample designs were conducted to identify mobile internet use factors and to test the moderating effects of disability on mobile internet use. ResultsOlder adults with disabilities used mobile internet less than older adults without disabilities. However, disability status had moderating effects on the relationships between mobile internet use and (1) operational skills regarding mobile devices (B=0.31, P=.004), (2) internet use skills (B=1.46, P<.001), (3) motivation to use digital devices (B=0.46, P=.01), and (4) attitude toward new technology (B=0.50, P=.002). The results revealed that these positive relationships were stronger among older adults with disabilities than among adults without disabilities. ConclusionsAlthough older adults and people with disabilities are considered vulnerable populations regarding technology adoption, disability creates a stronger association between several determinants and actual mobile internet use. Therefore, policy makers and practitioners should pay attention to older adults with disabilities to deliver appropriate information-literacy education. Older adults with disabilities could be the primary beneficiaries of mobile services and new technology.